Kesenian Singa Manuk dari Desa Anggasari Kabupaten Subang 2003-2015 - Muhammad Luthfi Abdul Aziz; Didin Saripudin (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2020)
This study aimed to describe the dynamics of Singa Manuk art in Anggasari Village, Subang Regency in 2003-2015. The researcher utilized historical methods, namely heuristics, criticism, interpretation, and historiography. Research’s technique by conducting field and literature studies. Based on the result, the emerge of Singa Manuk art in Anggasari Village was due to a mixture’s cultures between the Subang culture through its Sisingaan art and the typical Pantura dangdut music which was due to artists anxiety in Anggasari Village that such art will be faded. Thus new innovations rise, namely the Singa Manuk art. Singa Manuk art experienced dynamic development, starting from 2003 by Sanggar Genades until 2015. Singa Manuk art in Anggasari Village experienced continuous development and innovation by the artists in the village so that it continues to be favored mostly by the community and preserved. The effort to preserve the Singa Manuk art involves various parties, namely the artists, the district government, the village government as well as the community who take part in preserving the Singa Manuk art.